Crossmodal Processing of Haptic Inputs in Sighted and Blind Individuals - Voss, Patrice; Alary, Flamine; Lazzouni, Latifa; Chapman, C. E.; Goldstein, Rachel; Bourgoin, Pierre; Lepore, Franco (Frontiers in Systems Neuroscience, 2016)
In a previous behavioral study it was shown that early blind individuals were superior to sighted ones in discriminating 2-D tactile angle stimuli. The present study was designed to assess the neural substrate associated with a haptic 2-D angle discrimination task in both sighted and blind individuals. Subjects performed tactile angle size discriminations in order to investigate whether the pattern of crossmodal occipital recruitment was lateralized as a function of the stimulated hand. Furthermore, task-elicited activations were compared across different difficulty levels to ascertain the potential modulatory role of task difficulty on crossmodal processing within occipital areas. We show that blind subjects showed more widespread activation within the right lateral and superior occipital gyri when performing the haptic discrimination task. In contrast, the sighted activated the left cuneus and lingual gyrus more so than the blind when performing the task. We also show that activity within parietal and occipital areas was modulated by task difficulty, where the easier angle comparison elicited more focal occipital activity along with bilateral posterior parietal activity, whereas the more difficult comparison produced more widespread occipital activity with reduced parietal activation. Finally, we show that crossmodal reorganization within the occipital cortex of blind individuals was primarily right lateralized, regardless of the stimulated hand, supporting previous evidence for a right-sided hemispheric specialisation of the occipital cortex of blind individuals for the processing of tactile and haptic inputs that is independent of the lateralisation of the input.